Unaccompanied refugee minors and resilience: A phenomenological study - LEKKAI, INA (Przegląd Krytyczny, 2020)
Unaccompanied child migration, propelled by war, political strife and instability is an increasingly serious global problem. Refugee youth contends with numerous challenges as they adjust to living in a new country. Although their capacity for resilience is being given the deserved recognition, studies where their views are taken into account greatly outweigh in number those where the voices of young refugees directly narrate how they bounce forward in the face of an uncertain future (Walsh 2002). Resilience scholars are challenged to move beyond a narrow understanding of youth refugee resilience by conducting research on their life situations exploring their own perspectives. This article describes some of the insights gained from a phenomenological study— whose methods are particularly effective at capturing and illuminating the experiences and perceptions of individuals from their own perspectives— undertaken with unaccompanied minors living in Germany. The narrative approach used to explicate their narratives highlights seven major coping strategies: (1) Treasuring personal identity, (2) Maintaining cultural identity, (3) Networks of support and social negotiations, (4) Nurturing the need to belong, (5) Embracing a positive outlook, (6) Perceived self-efficacy and personal characteristics, (7) Adopting a growth mindset & self-enhancement expectations. The empirical data of this research show that URMs are active agents in choosing meaningful pathways to resilience and purposefully navigate through the numerous challenges in their lives.